Hukum Perkawinan dalam Perspektif Hukum Positif dan Hukum Islam - Meirina, Mega (Lembaga Yasin AlSys, 2023)
In the compilation of Islamic law, it is explained that marriage is marriage, which is a strong contract or mitsaqan ghalizhan to obey Allah's commands and carry it out is worship. The term marriage comes from Arabic, namely (النكاح), some say marriage according to fiqh terms used the words marriage and zawaj words. Meanwhile, according to Indonesian terms, it is marriage. Nowadays it is often distinguished between marriage and marriage, but in principle, marriage and marriage differ only in drawing the root of the word. The meaning of marriage according to the Shari'ah, marriage also means a contract. While the notion of intercourse is only a metaphor. The meaning of marriage here is the union of two people with different types, namely men and women who form a bond with an agreement or contract. The analytical descriptive method used in this research is to present an appropriate description regarding the function of multinational companies in economic development through foreign investment. The results of the study concluded that in the Indonesian-national legal system, Law No. 1/1974 and Presidential Instruction no. 1/1991 is a regulation that contains Islamic legal values, even KHI is an Indonesian fiqh which fully contains Islamic civil law material (marriage, inheritance and waqf), in the development of contemporary Islamic religious and family differences law, there have been many developments of thought, including in allow interfaith marriages.